Weekday Physical Activity and Health-Related Fitness of Youths with Visual Impairments and those with Autism Spectrum Disorder and Visual Impairments. (July 2018) - Haegele, Justin A.; Zhu, Xihe; Kirk, T. Nicole
Introduction: Youths with visual impairments (that is, those who are blind or have low vision), as well as those who are visually impaired and have autism spectrum disorder (hereafter, autism), tend to be physically inactive and have low health-related fitness. However, little is known about individuals with dual disabilities, such as those with autism and visual impairments. Thus, the aim of this study was to perform an initial exploration of physical activity and health-related fitness for these students in comparison to students with visual impairments alone. Methods: Twelve participants (six with visual impairments, six with autism and visual impairments) aged 8–16 years (Mage = 12.4) who came from a school for students with visual impairments were participants. Participants wore tri-axial accelerometers on their right hips for four consecutive weekdays, during waking hours, to measure weekday physical activity. Following that task, they completed four health-related fitness tests, including a half-mile walk or run to measure aerobic endurance, a push-up test to measure upper-body muscular endurance, a modified curl-up test to measure abdominal muscular endurance, and a sit-and-reach test to determine flexibility. Data were analyzed using descriptive statistics and independent sample t-tests to identify differences between groups. Results: On average, the participants accrued 650.17 ± 141.44 minutes of sedentary time, 129.80 ± 66.78 minutes of light physical activity, and 19.78 ± 3.35 minutes of moderate-to-vigorous physical activity per weekday. No participants met the 60-minute recommendations of daily moderate-to-vigorous physical activity. Participants with autism and visual impairments were significantly less physically active (p = .02) and less likely to pass fitness tests (p = .01) than were their peers with visual impairments alone. Discussion: This study provides the first empirical exploration of health-related variables for youths with autism and visual impairments. It is clear that developing and implementing interventions to help enhance physical activity and health-related fitness for those youths are needed. Implications for practitioners: Additional training and resources to understand the unique needs of these youths are essential in providing opportunities to participate in physical activities and enhancing health-related physical fitness.